(untitled) (Update Dental College Journal, 2019)
A 15 year old boy was presented with pain in his upper anterior teeth. On clinical examination both the maxillary central incisor revealed slight discoloration and fracture of the crown. Radiographic evaluation revealed open apex of the left central incisor and apex of the right central incisor was fully developed. Apexification with MTA apical plug was carried out in left central incisor and conventional root canal treatment was done in right central incisor. In two months follow up both the tooth were clinically and radiographically asymptomatic and the healing of the apical area of the left central incisor was continued. These finding suggests that MTA can induce formation of apical barrier in the case of non-vital tooth with open apex. Update Dent. Coll. j: 2019; 9 (1): 42-45